The myth of the rational market : a history of risk, reward, and delusion on Wall Street - Fox, Justin , 1964- (Petersfield, Hampshire : Harriman House, 2010)
Presents an account of the rise and fall of the efficient market theory and the century-long making of the financial industry. This book features the people and ideas that forged the finance and investing industry. It includes the tales of Wall Street's evolution and the Great Depression
1. Early days -- 2. The rise of the rational market -- 3. The conquest of wall street -- 4. The challenge -- 5. The fall
First published: New York : Harper Business, 2009
Includes bibliographical references and index
Keywords: Economics -- History; Economics -- Psychological aspects; Rational expectations (Economic theory)